Comparison of results of statistical analysis of health care for inpatients of Islamic hospitals in Padang city in 2019 - Sari, Rahmi Septia (International Journal Of Community Medicine And Public Health, 2020)
Background: The success of hospitals in providing services seen from the results of health care statistics, in the form of daily census, day of service, average length of stay (ALOS), bed occupancy rate (BOR), bed turnover rate (BTR), turnover interval (TI), coding disease diagnoses in the of Islam Islamic hospital. Methods: Research uses descriptive method with qualitative approach. Data collection technique used is the observation method that is direct observation of medical records and the method is done by collecting data from the Islamic Hospital in the city of Padang for processing statistical data. Results: During the period of June 1 to June 30, 2014 there were 330 outpatients, 127 bed units in IbnuSina while in Siti Rahmah outpatients were recorded 264 patients with 48 beds. From data it appears that the most patients entering in the city of Padang are Siti Rahmah with the difference in the number of patients 66 patients with 79 beds. And information is obtained that this is influenced by the availability of adequate facilities and services. Conclusions: The highest of patients from the Islamic hospital is Siti Rahmah with a diagnosis of dengue hemorrhagic fever (DHF) (A91), the main diagnosis frequency of chapter XI is 15.45% with the most patients coming from in Padang as many as 194 patients. From the results of statistical data, it can be analyzed that the TLOSis 1357 days and ALOS is 4.11 or 4 days. BOR is 32.94%, The BTR 2.60, TI 7.74 days.